Handsanitizer Mandiri Untuk Warga Desa Kedunguter, Kecamatan Banyumas, Kabupaten Banyumas - Miza Liyana Bte Moh Warid (Abdi Jaya : Jurnal Pengabdian Indonesia, 2025)
In response to the need for preventive measures against Corona, a workshop on making hand sanitizer was organized for the residents of Kedunguter Village, Banyumas. The activity, which involved direct guidance and surveys, aimed to help the community gain easier access to hand sanitizer and understand its importance in daily life. Following the training, participants demonstrated increased awareness and improved accessibility to hand sanitizer.